Seed Treatment With Systemic Fungicides: Time for Review - Ayesha, Mulla S.; Suryanarayanan, Trichur S.; Nataraja, Karaba N.; Prasad, Siddegowda Rajendra; Shaanker, Ramanan Uma (Frontiers in Plant Science, 2021)
Pre-sowing seed treatment with systemic fungicides and antibiotics is a firmly entrenched practice for most agricultural crops worldwide. The treatment is intended to protect the crop against seed and soil-borne diseases. In the recent years, however, this nearly century-old practice of seed treatment has come to be questioned, because of its unintended consequences on seed endophytes, many of which may play a role in seed development, seed germination, seedling establishment and ultimately crop performance. Here, we review these concerns and identify critical research gaps that need to be addressed to better appreciate the consequences of seed treatment and to explore alternative treatment protocols.